2018
DOI: 10.1080/21645515.2018.1502524
|View full text |Cite
|
Sign up to set email alerts
|

Non-uptake of childhood vaccination among the children of HIV-infected mothers in sub-Saharan Africa: A multilevel analysis

Abstract: The aim of this study was to develop and test models for non–uptake of three doses of diphtheria-tetanus-pertussis containing vaccines (DTP3) among children of women living with HIV in sub-Saharan Africa. The study used demographic and health survey data from 27 sub-Saharan African countries that have the required HIV and immunization data sets. Multivariable logistic regression models were used to assess the relationship between individual and contextual factors associated with non-uptake of DTP3 among the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This led to proposals for interventions that are focussed on young HIV-infected, unemployed women, those without formal education, individuals living in communities with high illiteracy rate and in countries with low adult literacy rate. 22 The need for community-engagement and a bottom-up approach that is cognisant of societal, cultural and religious considerations to address the barriers contributing to underimmunization of children was clearly also evident with the experience around polio eradication efforts in countries such as Nigeria, Pakistan and Afghanistan. A further example of this is the experience shared by Kpanake et al in this journal, on the hypothetical willingness of Guineans to be vaccinated against Ebola; with 25% of respondents not supporting vaccination, and a further 19% demonstrating hesitancy toward vaccination.…”
mentioning
confidence: 99%
“…This led to proposals for interventions that are focussed on young HIV-infected, unemployed women, those without formal education, individuals living in communities with high illiteracy rate and in countries with low adult literacy rate. 22 The need for community-engagement and a bottom-up approach that is cognisant of societal, cultural and religious considerations to address the barriers contributing to underimmunization of children was clearly also evident with the experience around polio eradication efforts in countries such as Nigeria, Pakistan and Afghanistan. A further example of this is the experience shared by Kpanake et al in this journal, on the hypothetical willingness of Guineans to be vaccinated against Ebola; with 25% of respondents not supporting vaccination, and a further 19% demonstrating hesitancy toward vaccination.…”
mentioning
confidence: 99%
“…Overall, 23 (18%) studies used DHS datasets from multiple countries, ranging from 2 [17][18][19] to 86 countries. 11 Seven studies used data from multiple African countries, [20][21][22][23][24][25][26] 4 from just Asian countries, 17 18 27 28 1 from the Americas 19 and the remainder (11) used data from multiple continents. 10-12 29-36 For one study, we were unable to determine what exact countries were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In recent times, studies have explored the predictors and barriers to immunisation or full immunisation while series of reviews have been conducted on this subject. Some of these recent studies have reported that lack of knowledge of immunisation, lack of partner support, financial deprivation and distrust in immunisation programmes account for incomplete or nonimmunisation [23][24][25] . Nigeria is a major contributor of global childhood death from vaccine preventable deaths.…”
Section: Under-5 Out-patient Attendance In Phcsmentioning
confidence: 99%